Bimbingan klasikal : layanan bimbingan konseling dalam pendidikan karakter siswa sma dengan metode brain storming - Sumiatun (Ikatan Bimbingan dan Konseling Sekolah)
Indonesia is currently in the midst of a nation character crisis. Currently the face of the Indonesian nation is still tarnished with a variety of events that are very alarming events, such as corruption cases, news stories hoax provoking the community, some people are still easily provoked, the occurrence of student brawl, bulliying cases, promiscuity, rape, drug abuse / NAPSA, the lack of exemplary leadership of several rulers, the lack of attention of parents to children, etc. SMA as a higher education institution is one of the most important resources to develop a curriculum that clearly includes character education. Given the condition of the problem as mentioned above, it is necessary government efforts to build national character based on religion and nation culture. For that it is appropriate for schools to provide character education for students/students. Classical guidance is one form of service that is very effective and liked by students, Character education through classical guidance with Brain Storming method is expected to be fun for learners and can run as expected.